Penanaman Akidah Melalui Pembiasaan Membaca Kitab Ta’limul Mubtadi’in Aqoid Ad-Diin di SD Negeri Kabupaten Tegal - fatmawati, Riza; Hammam, Hammam (Attractive : Innovative Education Journal, 2020)
The aimed is to determine the strategy, implementation, evaluation as well as supporting and inhibiting factors of the cultivation of creed through the habit of reading the Book Ta'limul Mubtadiin fi Aqoid Ad-in state elementary school in Tegal Regency. This research was a descriptive qualitative research. The data in this study were obtained through interviews, observation and documentation. The results of this study indicate that, first, the strategies used in this habituation were of three kinds, 1) traditional strategies, namely for schools that carry out habituation once a week consisting of elementary school (SDN) Talang 01 and SDN Lawatan 01, 2) free strategy, namely for classroom students low (I, II and III) given the freedom to follow habituation and this applies to all schools, 3) internal trans strategy which was a school that conducts habituation every day, consisting of SDN Rancawiru 02, SDN Kepandean 01, SDN Kepandean 02, and SDN SDN Jenggawur Secondly, the implementation of the planting of faith through the habit of reading the Ta'limul Mubtadiin fi Aqoid Ad-In Book in Tegal Regency Elementary School, there are various who do it every morning in the school yard, there are also those who carry out PAI learning in class. Third, the evaluation includes evaluation of program plans (related to the purpose of planting creed through habituation), process evaluation (evaluation of problems that arise during habituation), and final evaluation (related to the attainment of refraction goals). Fourth, the supporting and inhibiting factors of the cultivation of the creed came from parents, students, teachers, the government of Tegal Regency and the editors of the book Keywords: Cultivation, Faith, Habituation, Ta'limul Mubtadiin fi Aqoid Ad-In